2000
DOI: 10.1074/jbc.275.16.12313
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between Members of the CNC-bZIP Family and the Immediate-Early Protein IE2 of Human Cytomegalovirus

Abstract: The HCMV IE2 protein negatively autoregulates its own expression as well as represses the transactivation activity of p53. Using the repression domain of IE2 as bait in the yeast two-hybrid system, Nrf1 and Nrf2, members of the CNC-bZIP family, were found to be IE2-interacting proteins. Residues 331-448 encompassing the DNA-binding and the dimerization domains of Nrf1 are sufficient for the interaction. The interaction was further confirmed in vitro by a glutathione S-transferase pull-down assay and in vivo by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Yeast two-hybrid assays were performed as described [45]. GST pull-down, IP and western analyses were all carried out as indicated [54,73].…”
Section: Yeast Two-hybrid Gst Pull-down Ip Western Blotting and Lumentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast two-hybrid assays were performed as described [45]. GST pull-down, IP and western analyses were all carried out as indicated [54,73].…”
Section: Yeast Two-hybrid Gst Pull-down Ip Western Blotting and Lumentioning
confidence: 99%
“…Thus, recruitment of p48 to the viral DNA replication center cannot ensure the involvement of chromatin assembly activity. In our previous yeast two-hybrid assay to screen for IE2-interacting proteins [45], one of positive clones identified using the C-terminal half (aa 291-579) of IE2 as bait is the p150 fragment containing amino acids 87 to 938 (full-length p150: 938 residues). Here, we show that CAF1 interacts with HCMV IE2 through p150 in HCMV-infected cells and by this interaction CAF1 is mislocated to viral DNA replication foci to facilitate HCMV genome replication.…”
Section: Introductionmentioning
confidence: 99%
“…The templates were pCITE-YY1AP and its YY1AP deletion mutants. The protocol of GST pull-down has been described previously (28,29). After being washed with Buffer D (28), the bound proteins were eluted and analyzed by electrophoresis on a 10% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…We identified that the p150 fragment aa 87-938 interacted with the C-terminal half (aa 291-579) of IE2. Because proteins obtained using this strategy, such as Nrf1 and Nrf2 (24), antagonized the IE2-mediated transcriptional repression of its own promoter, the major IE promoter (MIEP), we examined if p150 has a similar effect. Unexpectedly, in the absence of IE2, p150, but not p60, increased the MIEP activity in a dose-dependent manner.…”
mentioning
confidence: 99%
“…Previously, a yeast two-hybrid assay was used to screen for proteins associating with the immediate early protein 2 (IE2) of the human cytomegalovirus (HCMV) (24). We identified that the p150 fragment aa 87-938 interacted with the C-terminal half (aa 291-579) of IE2.…”
mentioning
confidence: 99%